Ethanol fermentation from non-detoxified lignocellulose hydrolysate by a multi-stress tolerant yeast Candida glycerinogenes mutant. (February 2019) - Zhao, Meilin; Shi, Dingchang; Lu, Xinyao; Zong, Hong; Zhuge, Bin; Ji, Hao
Highlights: Candida glycerinogenes UG21, a multistress-tolerant yeast was obtained. UG21 exhibited highly-efficient degradation ability to furfural. High levels of acetic acid and furfural had little impact on UG21 ethanol fermentation of UG21. 1.24 g/L/h of ethanol productivity from non-detoxified sugarcane bagasse was obtained. UG21 could be used as platform for lignocellulose ethanol production. Abstract: The aim of this work was to study ethanol fermentation properties of the robust mutant Candida glycerinogenes UG21 from non-detoxified lignocellulose hydrolysate. C. glycerinogenes UG21 with high tolerance to elevated temperature, acetic acid, and furfural was obtained and applied in lignocellulose-based ethanol production. C. glycerinogenes UG21 exhibited highly-efficient degradation ability to furfural. High levels of acetic acid and furfural inhibited cell growths and ethanol production of Saccharomyces cerevisiae ZWA46 and industrial Angel yeast but had a slight impact on biomass and ethanol titer of C. glycerinogenes UG21. Using non-detoxified sugarcane bagasse hydrolysate, C. glycerinogenes UG21 reached 1.24 g/L/h of ethanol productivity at 40 °C but ethanol production of S. cerevisiae ZWA46 and Angel yeast was inhibited. Further, C. glycerinogenes UG-21 exhibited 2.42-fold and 1.58-fold higher productivity than S. cerevisiae ZWA46 and Angel yeast under low-toxicity hydrolysate. Therefore, C. glycerinogenes UG-21 could be an excellent candidate for low-cost lignocelluloses ethanol production.